2013
DOI: 10.1371/journal.pone.0082040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ENSO and Temporal Rainfall Variation on the Dynamics of Successional Communities in Old-Field Succession of a Tropical Dry Forest

Abstract: The effects of temporal variation of rainfall on secondary succession of tropical dry ecosystems are poorly understood. We studied effects of inter-seasonal and inter-year rainfall variation on the dynamics of regenerative successional communities of a tropical dry forest in Mexico. We emphasized the effects caused by the severe El Niño Southern Oscillation (ENSO) occurred in 2005. We established permanent plots in sites representing a chronosequence of Pasture (abandoned pastures, 0–1 years fallow age), Early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 75 publications
1
44
0
1
Order By: Relevance
“…The spatial signatures of these processes, however, have been distorted by the effects of natural and human-induced disturbances. All these processes have given rise to much higher rates of mortality and recruitment than those recorded over the first few years of succession in abandoned fields located in areas of dry (Maza-Villalobos et al, 2013) and wet (van Breugel et al, 2007) tropical climate.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial signatures of these processes, however, have been distorted by the effects of natural and human-induced disturbances. All these processes have given rise to much higher rates of mortality and recruitment than those recorded over the first few years of succession in abandoned fields located in areas of dry (Maza-Villalobos et al, 2013) and wet (van Breugel et al, 2007) tropical climate.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent dry years cause drastic reductions in population size. (Goldberg & Turner, 1986;Chesson et al, 2004;Villalobos et al, 2013;García-Cháves et al, 2014). In Northeastern Brazilian tropical dry forest areas, studies on the dynamics of caatinga herbaceous plants showed that populations may be dramatically reduced in their density, and may even disappear, from the habitats in drier years Lima et al, 2007;Santos et al, 2007;Silva et al, 2008;Santos et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there may be a reduction in seeds production during that season (Salo, 2004;Silva et al, 2008;Villalobos, Poorter, & Martínez-Ramos, 2013), which may compromise the size of populations in the subsequent year. An example of such reduction is observed in an annual grass, Bromus madritensis subsp.…”
mentioning
confidence: 99%
“…Second, large-scale studies of secondary forests indicate a strong effect of climate on the recovery rates of carbon and biodiversity (Anderson-Teixeira et al 2013, Poorter et al 2016, Rozendaal et al 2019. Third, longitudinal studies in secondary forests have revealed how droughts modulate recovery speed, increase mortality, and reduce recruitment and growth (Chazdon et al 2005, Maza-Villalobos et al 2013, Mart ınez-Ramos et al 2018, due to the negative effects on the water balance and photosynthetic rates of trees, especially in the earlier stages of succession (Bretfeld et al 2018).…”
Section: Introductionmentioning
confidence: 99%